Spring Sightings of Narwhal and Beluga Calves in Lancaster Sound, N.W.T. - Cosens, Susan E.; Dueck, Larry P. (ARCTIC, 1990)
During aerial surveys in 1986 of whales migrating in Lancaster Sound, we observed newborn narwhals as early as 27 May and regularly thereafter. Beluga calves were first seen on 31 May and were seen sporadically throughout the study period. These observations represent the earliest reported sightings to date of newborn narwhals.